Nowe zjawiska w sferze terminologicznych nominacji barw w języku rosyjskim - Narloch, Andrzej (Studia Rossica Posnaniensia, 2010)
The article presents an attempt at structural and semantic description of terminological colour names in Russian. The material comes from The Catalogue of Colour Names in Russian, design magazines and Internet. The names under study differ structurally. More and more often nouns and phrases function as colour terms. One of the most important functions of the new colour terms is the advertising function. Many units are marked stylistically and emotionally.